Comparative queer methodologies and queer film festival research. Issue 1 (2nd January 2018) - Binnie, Jon; Klesse, Christian
Abstract: This paper examines how a critical examination of the queer politics of comparison can inform queer film festival research. The discussion of the queer politics of comparison draws on a qualitative study of five queer film festivals in different European cultural geopolitical contexts which examined these festivals as sites for the reproduction of queer visibility, solidarity and queer space. We propose an approach of relational comparison within a framework that highlights regional contextuality. We further argue that queer approaches to comparative research should be informed by postcolonial critiques that challenge hegemonic notions of temporality and spatiality within political geographical imaginaries of Europe. We therefore suggest that poststructural and postcolonial informed perspectives on 'cultural translation' are key to the queering of comparison. Such an approach to cultural translation critical self-reflexivity within a transversal hermeneutics that at the same time pay attention to geopolitics, positionality and difference.